Carbon Nanofibers Fabricated from Electrospun Nano-sized boron oxide/Polyacrylonitrile Nanofibers as electrode for Supercapacitors - Ümran Kurtan (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
Porous carbon nanofiber (CNF) composites are promising electrode materials for supercapacitor (SC) applications. In this research, for the purpose of developing efficient CNFs with high specific capacitance, PAN solutions introduced with nano-sized boron oxide (B2O3) were electrospun followed by thermal treatment at high temperature. The best electrochemical performance was found for the sample which was doped 1 wt% nano-sized boron oxide and a gradual decrease was seen when the content was increased from 1 to 5 wt%. 1BCNF electrodes prepared from 1 wt% nano-sized boron oxide with PAN show a remarkable specific capacitance of 146 Fg-1 at 1Ag-1 compared to the pure CNF which is 46 Fg-1. Also, 1BCNF composite has an excellent cycle life which is more than 90 % capacity retention after 6500 cycles. The results showed that 1BCNF composite is a promising potential electrode for supercapacitor applications due to the optimized pore structure and enhanced electrical conductivity.